The prevalence of relative age effects and the influence of the talent pool size on Australian male and female youth football - Bennett, K. J., Novak, A. R., Fransen, J., Duffield, R. (Journal of Sports Sciences, 2023)
The current study explored the association between talent pool size and relative age effects in Football Australia`s talent pathway. It also compared relative age effects between male and female players. Participants were 54,207 youth football players (females: n = 12,527, age-range = 14.0-15.9; males: n = 41,680, age-range = 13.0-14.9) eligible for the National Youth Championships. We developed linear regression models to examine the association between the member federation size and the probability of a player being born earlier in the year. We also analysed selection probabilities based on birth quartile and year half across three layers. Overall, talent pool size was associated with a higher probability of selecting a player born in the first half of the year over the second. More specifically, an increase of 760 players led to a 1% higher selection probability for those born in the first six months of a chronological age group. In addition, there were more occurrences of relative age effects in the male than the female sample. Future studies should focus on the impact of the talent pool size on relative age effects at each major talent identification/selection stage of a talent pathway.